Reichsparteitag Nürnberg Postkarte Ansichtskarte Bund Deutscher Mädel... - Uncredited illustrator (Wikimedia Commons, 1936)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Postkarte Ansichtskarte Bund Deutscher Mädel HJ-BDM NSDAP Burg Propaganda Nazi Party Nuremberg Rally Postcard Uncredited artist No known copyright restrictions 675447-000000. " Nuremberg Rally " (Reichsparteitag Nürnberg). German postcard with painting of a uniformed member of the League of German Girls (Bund Deutscher Mädel, BDM), Swastika flag (Hitler Youth flag), and the Nuremberg Castle | Published by Photo-Hoffmann, Munich, Nazi Germany in 1936 | Nazi Party (NSDAP) propaganda | No signature (uncredited artist) and No known copyright restrictions.
Droits : Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château; Carte postale